Single-molecule imaging correlates decreasing nuclear volume with increasing TF-chromatin associations during zebrafish development - Matthias Reisser (Nature Portfolio, 2018)
Zygotic genome activation (ZGA), the onset of transcription after initial quiescence, is a major developmental step in many species. Here authors use single molecule tracking in live developing zebrafish embryos to show that increased transcription factor binding to DNA at ZGA is due to a shrinking nucleus.